Portrait Of Tolerance and Religious Harmony of Muslims and Hindus in Ngejot Tradition in Golong Village, West Lombok Regency - Muhammad Yuslih; Ahmad Muhajir (Fenomena, 2023)
This study aims to reveal the portrait of tolerance and religious harmony practiced by the Golong village community between Muslims and Hindus through the Ngejot tradition. The study departs from Indonesia's many religious conflicts, especially on the island of Lombok. The clashes occurred because of the lack of religious tolerance of the Sasak people. Amid many disputes that arise, the Golong village community has its way of maintaining religious harmony, namely through the Ngejot tradition. The research is included in the type of field research (field research) because the data is collected through explanations or answers from informants. Data sources The data in this study were obtained from religious leaders, humanists, and people who have a broad understanding of the tradition of Ngejot. The data collection is done by interview, observation, and documentation methods. The results of this study indicate that the Ngejot tradition carried out by two religions, namely Islam and Hinduism, aims to strengthen the bonds of brotherhood and kinship that have long been built by their ancestors who have noble ideals to create a harmonious life. This tradition is not just about giving or delivering food to each other on religious holidays but goes beyond the meaning of tolerance itself. Islamic and Hindu religious communities not only respect each other and respect each other's rights but are also actively involved in realizing a tolerant and harmonious attitude to life. This is evidenced by mutual assistance to secure each other's religious activities on significant days such as Eid al-Fitr, Adha, takbiran marches, Kuningan, Odalan, and other religious social activities. They help each other without having to be hindered by religious barriers. Because for them, both Muslims and Hindus are basemen (brothers). Free For Article Collaboration With 2 Countries.